ANALYSIS OF CHANGES IN LAND USE IN 2005 UNTIL 2015 IN THE PENIRAMAN VILLAGE SUNGAI PINYUH SUBDISTRICT MEMPAWAH DISTRICT - SANJAYA, PANDI; Ir. H. Riduansyah, MP, Ir. H. Riduansyah, MP; Ari Krisno Hadi, SP., M.Si, Ari Krisno Hadi, SP., M.Si (Jurnal Sains Pertanian Equator, 2017)
ABSTRACT The rapid population growth requires increasing number of residential areas and for land use conversion on agricultural production. This study aims to Know extensive changes in land use in 2005 and 2015, Knowing paddy land-use changes in 2005 and 2015 as well as land use change Assessing the level of rice production as well as reference information to calculate an estimate of rice production. This research was conducted in the village of Peniraman, Subdistrict Sungai Pinyuh, Subdistrict Mempawah, West Kalimantan Province. The duration of the study period commencing from April 16 2016 until May 16 2016. The shomed that in 2015 dominate land use plantation, (1665.31 ha), or 64.55% of the area of "‹"‹the village of Peniraman. The smallest land use were residential (5.35% or 137.19 ha area) In 2015 forest area were "‹"‹375.89 ha, or 14.57% of the total area of "‹"‹the Village Peniraman. Paddy filds were western part of the village Peniraman were "‹"‹ 249.75 ha large area, or 9.67% of the total area of "‹"‹the Village Peniraman. Land use chanse since 2005 to 2015 showed that the land use change is an area of "‹"‹607.9 ha or 23.56% of the area of "‹"‹the village of Peniraman, has been converted to other land use type. Paddy production of the calculation of land productivity (ton / ha / 10 year) of agricultural land obtained an average productivity of the land by 3.55 ton per ha per year. if effected on a paddy field area Ekssesting 249.75 ha with the equality productivity, this value indicates that the hectarage, can produce as much as 3443.5 ton of paddy.